Designing the EIC electron storage ring lattice for a wide energy range. Issue 1 (1st January 2023) - Marx, D; Berg, JS; Cai, Y; Gamage, BRP; Hoffstaetter, GH; Kewisch, J; Li, Y; Montag, C; Morozov, V; Nosochkov, Y; Ptitsyn, V; Sagan, D; et al.
Abstract: The Electron-Ion Collider (EIC) will collide electrons with hadrons at center-of-mass energies up to 140 GeV (in the case of electron-proton collisions). A 3.8-kilometer electron storage ring is being designed, which will store electrons with a range of energies up to 18 GeV for collisions at one or two interaction points. At energies up to 10 GeV the arcs will be tuned to provide 60 degree phase advance per cell in both planes, whereas at top energy of 18 GeV a 90 degree phase advance per cell will be used, which largely compensates for the horizontal emittance increase with energy. The optics must be matched at three separate energies, and the different phase-advance requirements in both the arc cells and the straight sections make this challenging. Moreover, the spin rotators must fulfill requirements for polarization and spin matching at widely different energies while satisfying technical constraints. In this paper these challenges and proposed solutions are presented and discussed.